Sexual liberation, socialist style : communist Czechoslovakia and the science of desire, 1945-1989 - Lišková, Kateřina 1976- (Cambridge University Press, 2018)
"In communist Czechoslovakia, there were two distinct approaches to sexuality and gender. The first one went like this: sex should occur between equals, and men and women should be equal and free of the bourgeois shackles of property. Indeed, before entering into marriage, people were expected to get to know each other, whether in the workplace or at collective volunteer work units. The other approach to sexuality claimed the following: Men and women are fundamentally different and marriage only works if men are superior to women. That is, if gender arrangements are not ordered this way, women will suffer in a way similar to sexual dissatisfaction. In this approach, it is one's nuclear family and spouse that are the only safe social bonds. These types of statements capture the attitudes towards sex, gender, and family as they changed throughout the years in Czechoslovakia. The first approach to sexuality and gender is characteristic of the long 1950s, i.e. the period since the communists took power in 1948 until the early 1960s when discourses began to shift. The second approach, from the 1970s, sums up the attitude of the period called 'Normalization' which followed the failed attempts of the Prague Spring of 1968. This book tracks what it took to get from one approach to the other"--